The Overview of Anatomical Variations and Congenital Anomalies of the Uterine Tubes and Their Impact on Fertility - Csöbönyeiová, M; Klein, M; Feitscherová, C; Pavlíková, L; Kachlík, D; Varga, I (Physiological research, 2022)
Anatomical variations and congenital anomalies of the uterine tubes (UTAVsCAs) are rare conditions, which are often undiagnosed, or accidentally diagnosed upon imaging, laparotomy, laparoscopy for unrelated condition, or during the Cesarean section. UTAVsCAs are often asymptomatic, but their clinical relevance lies in their possibly adverse impact on fertility. Since their rare occurrence, they are usually published as case reports. The most typically described are: agenesis of the uterine tubes (UTs), accessory UT (UT duplication), accessory UT ostium, and paratubal cysts (e.g. the hydatid cyst of Morgagni). UTAVsCAs are classified into an umbrella category of Müllerian duct anomalies (MDAs) which comprises anomalous development of all the organs developing from the paramesonephric (Müllerian) ducts, i.e., UTs, uterus and upper portion of the vagina. Interestingly, most of the classification systems of MDAs discuss solely the uterine and vaginal anomalies, while the UTs are often utterly ignored. This probably originates from the fact that UTs are no longer interesting for many clinicians as they think of UTs as superfluous organs whose function can be easily replaced in the in vitro fertilization (IVF) laboratory. Indeed, the modern reproductive medicine has been helping enormously with the conception of infertile couples. In many instances, the UTs are in fact successfully bypassed and a "test-tube" baby is born. Nevertheless, the UTs are still absolutely unique in providing suitable environment for fertilization and early embryo development - processes that hasn´t been still completely understood. This fact could partially explain why the success rate of IVF is "only" around 30-50 % depending on age. Therefore, the research of the UTAVsCAs is still clinically relevant in the context of reproductive medicine and should not be omitted from research endeavors.
Keywords: Fallopian Tubes; císařský řez; Vagina; vagina; uterus; ženské pohlaví; Cesarean Section; Humans; Pregnancy; Female; Fertility; těhotenství; fertilita; vejcovody; lidé; Uterus